Comparative Analysis of Methicillin-Resistant Staphylococcus pseudintermedius Prevalence and Resistance Patterns in Canine and Feline Clinical Samples: Insights from a Three-Year Study in Germany - Leonie Feuer; Stefanie Katharina Frenzer; Roswitha Merle; Wolfgang Bäumer; Antina Lübke-Becker; Babette Klein; Alexander Bartel (MDPI AG, 2024)
The emergence of methicillin-resistant Staphylococcus pseudintermedius (MRSP) presents a significant public health concern globally, particularly within veterinary medicine. MRSP's resistance to multiple antibiotics is limiting treatment options and potentially leading to severe infections in companion animals. This study aimed to understand antimicrobial resistance in dogs and cats, focusing on MRSP resistance patterns and its prevalence in Germany. We analyzed results of bacterial diagnostic samples from canines and felines, sourced from a German veterinary diagnostic microbiology laboratory between 2019 and 2021. This dataset included samples from 3491 veterinary practices, covering 33.1% of veterinary practices and clinics in Germany. MRSP rates were detailed by host species, sample types and co-resistance patterns. Analysis of 175,171 bacterial examination results revealed S. pseudintermedius in 44,880 samples, yielding a 25.6% isolation rate. S. pseudintermedius was more prevalent in dogs (35.0%) than cats (3.6%). Methicillin resistance was found in 7.5% of all S. pseudintermedius isolates. MRSP prevalence was higher in feline samples (16.1%, 95% CI 14.4-17.8) compared to canine samples (7.1%, 95% CI 6.8-7.0). S. pseudintermedius showed high resistance rates to ampicillin (cats: 48.6%, dogs: 67.6%) and clindamycin (cats: 37.2%, dogs: 32.7%), while MRSP exhibited high co-resistance to clindamycin (cats: 82.8%, dogs: 85.4%) and sulfamethoxazole + trimethoprim (cats: 66.4%, dogs: 66.2%). Our study revealed distinct resistance patterns of MRSP in cats compared to dogs, highlighting the need for tailored treatment approaches and the importance of antimicrobial resistance surveillance.